Confiança na gestão de equipes de alto desempenho da indústria farmacêutica - Gomensoro, Eduardo Eugênio Bittencourt de (2015)
In the pharmaceutical industry relationships based on trust are fundamental for work team function in all levels. There is a strong impact of change, and derived uncertainty, in the trust dynamics between the work teams and their motivation. In recent academic production, the liaisons between trust and performance have been explored and, particularly, we bring forth the results of the first empirical research conducted in Brazil to measure the interpersonal trust levels, trust indicators and employee commitment inside a representative sample of private sector Brazilian organizations. The organizations researched and compared by Prof. Marco Túlio Zanini were selected as being representative of the 'new' and 'old' economies, among which the main differentiators are the knowledge management and the high level of uncertainty secondary to the frequent organizational and environmental change. These aspects associate companies of the research-based pharmaceutical industry to companies of the 'new' economy, in accordance to Prof. Zanini’s study. Companies of the pharmaceutical industry are going to implement important changes in their ways of doing business in the coming years, most of all in which concerns their communication, promotion and management of commercial work teams, and this seems to be a particularly interesting time for a study like the described in this dissertation. The aim of this work was to determine the level of similarity between the trust indicators among a commercial workforce from the biotechnological product segment (vaccines) of a major global organization of the research-based pharmaceutical industry, and the indicators obtained from organizations of the 'new' economy. We intended to measure the interpersonal trust and commitment indicators among the commercial workforce of the organization, in order to access the effects of enterprise uncertainty upon them. Our research tools were a previously validated survey, conducted upon the whole promotional team (56 members) of a specific area of the studied organization; public and private company data (the company remains undisclosed and identified as Company 'J'), and complementary in-depth interviews with key managers of the subject team: national and regional managers. Some similarity was found between the trust and commitment indicators of the companies of the 'old' economy and the indicators from Company 'J', for most of the evaluations. Nevertheless, some resemblance was also found between the indicators from companies of the 'new' economy and Company 'J', most of all among the managers of the latter. This could be an indicator of the impact of some measures recently implemented by Company 'J', which could have increased organizational uncertainty and instability. From the acquisition, analysis and comparison of this indicators we propose some discussion on the impact of the recent changes implemented on the relational work contract within Company 'J' and the relative relational dynamics inside its commercial workforce.